Postpartum care in labor with indication of premature rupture of membranes - Zulfiah, Rikha Lailatuz; Rahayuningsih, Faizah Betty (Institute of Computer Science (IOCS), 2024)
Premature rupture of membranes (PROM) is an obstetric condition that occurs when the amniotic sac ruptures before 37 weeks of gestation, which can increase maternal and neonatal morbidity and mortality, thus requiring special attention in postpartum management. This study aims to explore appropriate postpartum care for patients experiencing PROM, with a focus on pain management, monitoring vital signs, and educating about postnatal warning signs. Using an evidence-based literature review method, 25 articles published between 2018 and 2024 were analyzed. The findings indicate that nursing interventions based on the Nursing Outcomes Classification (NOC) and Nursing Interventions Classification (NIC) can improve functional patterns in patients, although there is still a risk of complications such as uterine atony and postpartum hemorrhage. Emotional and psychological support were also identified as essential elements in postpartum care. This study emphasizes the need for a holistic approach in postpartum care to ensure optimal recovery and minimize long-term complications for both mother and baby.